Mepolizumab for hypereosinophilic syndrome: effectiveness and safety from real-world evidence - Mora, Elvira; Fox, María Laura; Lemes, Angelina; Velasco, Beatriz; Hernández-Rivas, Jesús María (Frontiers in Immunology, 2025)
Hypereosinophilic syndrome (HES) is a rare condition characterized by elevated eosinophil levels and related symptoms of eosinophil-mediated organ damage. We reviewed the effectiveness and safety of mepolizumab for the treatment of HES. A scoping review was conducted following the PRISMA Scoping Reviews Checklist to identify real-world evidence of mepolizumab use in HES. In total, 36 references were identified as relevant and selected for review. Overall, 105 patients previously treated with glucocorticoids received mepolizumab at different dosages (range: 100–750 mg), routes of administration (subcutaneous/intravenous), and schedules (every 2–12 weeks). Remission rates were 57.1–76.0%. Most studies reported a range of 71.4–99.1% reduction in mean blood eosinophil counts with mepolizumab treatment. In addition, a glucocorticoid-sparing effect was observed; 85.7% of patients discontinued glucocorticoids after 12 months of mepolizumab administration. Mepolizumab was considered safe and well-tolerated and severe adverse events were rare. Mepolizumab provided clinically significant benefits in patients with HES in a real-world setting.